Principles of geographical information systems - Burrough, Peter A.; McDonnell, Rachael A. (Spatial information systems and geostatistics, 1998)
Provides a comprehensive introduction to the theory and practice of Geographical Information Systems (GIS). This work explains the theory and technical details behind GIS and provides the information necessary to understand why spatial information data and the information systems based on them are important in the modern world